Variability and rotation of young low mass stars: the case of the Cygnus OB2 Association - Julia Maria Torres Roquette (2017)
Photometric variability is one of the main characteristics of young stellar objects and explore its particularities in different wavelengths may provide insights on the ongoing physical processes at work in such objects. The most common source of photometric variability in young stars is the brightness modulation, caused by the rotation of a spotted stellar surface. This type of variability allows to measure rotation periods in young stars. In the last decades, the early evolution of pre-main sequence stellar rotational picture has been constrained by studies targeting different young regions at a variety of ages. Observational studies suggest a dependence of rotation with mass, and for some mass ranges a connection between rotation and the presence of a circum stell ardisc. Not still fully explored, though, is the role of environmental conditions on the stellar rotational regulation. In this thesis, we explored the occurrence and main characteristics of near-infrared variability for young stars of the massive OB association Cygnus OB2, which is 1.4 kpc away from the Sun. For objects with periodic variability that could be associated with stellar rotation, we investigated the rotational properties of Cygnus OB2 members. For the sample of rotational periods evaluated, we addressed questions regarding the effect of environment properties on the pre-main sequence rotational evolution. We investigated JHK-band variability of 5083 candidate members (24% of which are disc-bearing stars), using data observed with the wide-eld camera (WFCAM) of the UK Infrared Telescope (UKIRT) on Mauna Kea, Hawaii. A total of 112 nights were observed, spanning 217 days. The sample studied is spread over a eld of 0.78 squared degrees. The selection of variable stars was done by using Stetson variability index, and 60% of the stars in the sample were found to be variable according to this criterion. We investigated the light-curve morphology, and the variations in the colour-colour and colour-magnitude diagrams for JHK-bands, and when the variability was highly correlated in different bands and colours, the slopes produced by the variations inside such diagrams were estimated. These slopes were compared to the slopes expected from the models explaining physicalmechanisms responsible by the variability in young stars, and the causes of variability were investigated. Period search was performed using Lomb-Scargle periodogram for periods between 0.8345 days. Period detection quality was veried by using False Alarm Probability levels, the Saunders statistics, string/rope length method, and visual verication of folded light curves. We identied 1224 periodic variable stars. Monte Carlo simulations were performed in order to evaluate completeness and contamination of the periodic sample, out of which 894 measured periods were considered as reliable. Our study was considered reasonably complete for periods between 2 and 30 days. The general scenario for the rotational evolution of young stars seen in other regions is conrmed by Cygnus OB2 period distributions, with disc-bearing stars rotating on average slower than stars without discs. A mass-rotation dependence was also veried, but as in NGC 6530, very low mass stars (M <0.4M ) are rotating on average slower than higher mass stars (0.4M < M <1.4M). We observed an excess of slow rotators among the lower mass population. The disc and mass-rotation connection was also analysed by taking into account the incident UV radiation arising from O stars in the association. Results compatible with the disc-locking scenario were veried for stars with low UV incidence, but no statistical signicant relation between rotation and disc presence was veried for stars with high UV incidence, suggesting that massive stars can have an important role on regulating the nearby low mass stars rotation.